Social status-dependent regulation and function of the somatotropic axis in juvenile rainbow trout - Mennigen, Jan A.; Magnan, Julianne; Touma, Kenan; Best, Carol; Culbert, Brett M.; Bernier, Nicholas J.; Gilmour, Kathleen M. (Molecular and cellular endocrinology, 2022)
Juvenile rainbow trout (Oncorhynchus mykiss) develop social hierarchies when competing for resources in a constrained environment. Among the physiological consequences of social status are changes in organismal energy metabolism, which generally favour anabolic pathways in dominant fish and catabolic pathways in subordinate fish. The somatotropic axis is an important regulator of metabolism and growth that could be involved in mediating metabolic changes in response to social status in juvenile rainbow trout. Here we used juvenile trout housed either in dyads or individually (sham controls) to determine whether social status changes indices of somatotropic axis function. Although pituitary growth hormone expression (gh1 and gh2) did not differ among groups, circulating growth hormone (GH) increased ∼12-fold in subordinate fish compared to sham and dominant fish. Social status caused consistent differential expression of GH receptor paralogues in liver and muscle, two principal target tissues of GH. Compared to dominant and/or sham fish, ghra paralogue expression (ghra1 and ghra2) was lower, while ghrb1 expression was higher in subordinate fish. Across tissues, ghra paralogue expression was generally positively correlated with expression of insulin growth factors (igf1, igf2), while ghrb1 expression was positively correlated with transcript abundance of hormone sensitive lipase (hsl1). Because igf and hsl expression are subject to context-dependent GH control in rainbow trout, these results suggest that increased circulating GH in conjunction with differential expression of ghr paralogues may translate into prioritization of downstream catabolic lipolytic pathways in subordinate rainbow trout. These findings support a social context-dependent role for GH signalling in mediating metabolic changes in juvenile rainbow trout. •Social status-dependent regulation of somatotropic axis in juvenile rainbow trout.•Subordinate rainbow trout exhibit increase in circulating growth hormone.•Subordinate fish generally induce ghrb paralogues and lipolytic hsl1.•Dominant fish generally induce ghra paralogues and anabolic igf1/igf2.•Results suggest ghr paralogue-specific regulation of anabolic and catabolic GH effects.